The Relationship between Resilience and Work-Study Conflict in Working Students - Najwa Najwa; Eka Dian Aprilia; Irin Riamanda; Marty Mawar Puri (IJIP : Indonesian Journal of Islamic Psychology, 2023)
In addition to having a busy course in college, some students also have activities outside of college; have a job. Dense lecture activities and busy work carried out can cause work-study conflicts in students. Work-study conflict is a work activity that interferes with student learning activities to meet demands and obligations related to school or campus. One of the factors that can reduce work-study conflict is resilience. The purpose of this study was to determine the relationship between resilience and work-study conflict. This study used quantitative methods with a correlation approach. The data collection procedure uses a nonprobability sampling technique of accidental sampling type with a sample of 170 people collected using google research form. The research measurement tool used the Work Study Conflict Scale (WSCS) with Alpha Croanbach (α) 0.777 and the Connor Davidson Resilience Scale (CD-RISC) with Alpha Croanbach (α) 0.930. The hypothesis test was carried out using the Spearman Correlation technique, obtaining a significance value (p) = 0.471 (p<0.05). The results showed there is no negative relationship between resilience and work-study conflict in working students. In addition, the results also showed that the majority of research subjects were in the high work-study conflict category and the high resilience category.